Media Baru Dan Fesyen( Studi Deskriptif Kualitatif Tahapan Imitasi Fesyen Wak Doyok Melalui Instagram) - Priaditama, Hidayat Khairu; , Agus Triyono, M.Si (2017)
The use of internet such as sosial media of instagram countinously can cause the emergence of imitation behaviour between people. Instagram is used because it is a picture and video-based sosial media and very popular today. In instagram, there are a lot of people who use this application with varios puposes. One reason why people use instagram is because they can take instagram as a fashion references. Wak Doyok is one of Classical Fashion icon which is booming nowdays with one million followers. With the exchanging information in instagram like classical fashion style of Wak Doyok, there is imitation process of fashion styles done by the followers of Wak Doyok. This reserach aimes to know the phases of Wak Doyok fashion style through instagram. This research applied qualitative descriptive method. Data collection used in depth interview and interviewees were selected by purpossive sampling technique. The analysis data used resource tringaulation method. The result of the research showed that the stages of the fashion style imitation of Wak Doyok done by the followers of Wak Doyok was done in four stages; Stages of attention, retention, reproduction stage of motor, stage of motivation. These four factors encouraged Wak Doyok followers to imitate Wak Doyok fashion style in instagram.